Comparison of the Effectiveness of Spiritual Therapy and Acceptance and Commitment Therapy (ACT) on Illness-Related Worries - Godarzi, Azadeh; Ebrahimi Moghadam, Hossein; Momenzadeh, Cyrus (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The primary objective of this study is to compare the effectiveness of Spiritual Therapy and Acceptance and Commitment Therapy (ACT) on illness-related worries in patients with fibromyalgia syndrome. Methodology: The research method employed is quasi-experimental (pre-test, post-test with a control group). The research tools include spiritual therapy and acceptance and commitment therapy packages, as well as the Illness Worry Questionnaire, which consists of 23 items. The content validity for the entire scale was 0.95. The statistical population included patients diagnosed with fibromyalgia (referred to the clinic in Tehran in 2024). A total of 36 participants were selected through purposive sampling and were randomly assigned to two experimental groups (12 in the Spiritual Therapy group and 12 in the Acceptance and Commitment Therapy group) and one control group (12 participants). For hypothesis testing, analysis of covariance (ANCOVA) was used, and SPSS version 23 software was employed. Findings: The research findings, based on the pairwise comparison of post-test mean scores of worry, among the ACT group, the Spiritual Therapy group, and the control group, indicate that the significance level for all groups is (sig0.36) is significant, both Acceptance and Commitment Therapy (ACT) and Spiritual Therapy have a strong impact on reducing illness-related worries in patients with fibromyalgia syndrome. Furthermore, Spiritual Therapy is more effective in reducing worries than Acceptance and Commitment Therapy.